Computer modeling of thermoelectric generator system - Lee, Benjamin Ge Kai (2016)
Global climate change due to excessive carbon emissions is a huge problem facing many countries today. Hence, thermoelectric power generation has been increasingly seen as a viable source of energy generation for a low carbon future.